Experimental Investigation on the Impact of Aeration Rate and Stirrer Speed on Micro-Aerobic Batch Fermentation - Liew, Emily; Nandong, Jobrun; Samyudia, Yudi (Asian Network for Scientific Information, 2009)
The impact of aeration rate and stirrer speed on micro-aerobic fermentation is studied at laboratory scale. Result suggests that with Baker's yeast, an increase in aeration rates from very low value can improve bioethanol productivity and yield because it can enhance cell viability. At constant stirrer speed of 150rpm, the increase in aeration rate from 1LPM to 1.5LPM leads to proportional increase in peak oxygen uptake rate (OUR) from 600mM/L.h to 1000mM/L.h. This increase coincides with the increase in yield by 7.5%. Interestingly at constant aeration rate of 1.5LPM, an increase in stirrer speed from 150 rpm to 250rpm leads to decrease in peak OUR from 1000mM/L.h to 457mM/L.h but increase in yield by 64%. In conclusion, both stirrer speed and aeration rate are important factors which have complex impacts on hydrodynamics and microbial metabolism, which in turn affect productivity and yield. Further work using CFD modeling and simulation method is required to gain better insights into how aeration rate and stirrer speed affect metabolism via the mixing mechanisms in a bioreactor.